Differential equations : a first course on ODE and a brief introduction to PDE - Ambrosetti, Antonio; Ahmad, Shair (Boston : Walter de Gruyter, 2024)
The 2nd edition also includes some new problems and examples. An effort has been made to make the material more suitable and self-contained for undergraduate students with minimal knowledge of Calculus. For example, a detailed review of matrices and determinants has been added to the chapter on systems of equations. The second edition also contains corrections of some misprints and errors in the first edition.
Includes Bibliography and Index
Keywords: Differential equations, Linear; 9; Differential equations